The THE CONNECTION BETWEEN INTERPRETATION AND LOCAL CULTURE: The Meaning of Jihad Verses in the Sundanese Interpretation of “Ayat Suci Lenyepaneun” in an Effort to Religious Moderation - Azkia Falsa Annaba (Journal of Ulumul Qur'an and Tafsir Studies, 2023)
Azkia Falsa Annaba. THE CONNECTION BETWEEN INTERPRETATION AND LOCAL CULTURE: The Meaning of Jihad Verses in the Sundanese Interpretation of “Ayat Suci Lenyepaneun” in an Effort to Religious Moderation. This bachelor thesis analyzes the relationship between interpretation and local culture in the context of Islam, especially regarding the interpretation of jihad verses in texts "Ayat Suci Lenyepaneun" among the Sundanese people. The main purpose of this thesis is to understand how local interpretations influence the understanding of the meaning of jihad verses and their impact on efforts to create religious moderation. The importance of understanding the relationship between interpretation and local culture in understanding religious teachings. This is relevant because cultural diversity and social context can affect a person's understanding of the holy text, especially in the case of jihad verses that can often be misinterpreted. The local cultural theory of Muntaj Tsaqofy Nasr Hamid Abu Zayd and the Theory of Interpretation of Double Movement by Fazlur Rahman became the basis for analysis in examining how Sundanese people understand and apply jihad verses in texts "Ayat Suci Lenyepaneun". Concepts such as local cultural recklessness influence how interpreters interpret things and Qur'anic interpretive approaches seeing the current context to the context of verses handed down and contextualized to the present times are important in understanding the interaction between religious and cultural interpretations. Research is conducted through in-depth analysis of the text "Ayat Suci Lenyepaneun" which focuses on the verses of jihad in Hasim's interpretation in his tafsir. Then discussed with a religious moderation approach from the various meanings of the jihad verse with a Sundanese flavor approach. The results of the analysis show that the Sundanese Interpretation has a unique interpretation of jihadist verses based on their local culture. This understanding tends to emphasize spiritual aspects and peaceful values, reflecting their efforts in promoting religious moderation and away from interpretations that encourage conflict. By understanding how the interpretation of jihadi verses is influenced by local culture, religious and community leaders can develop a more inclusive and culture-based approach to teaching religious teachings that promote tolerance, peace, and inter-religious cooperation. This bachelor thesis provides new insights into the relationship between interpretation and local culture in the context of Islam among Sundanese people. By exploring the meanings of jihad in Lenyepaneun's interpretation of the Holy Scriptures, this thesis contributes to the discussion of efforts to achieve more sustainable and inclusive religious moderation in a multicultural society.